Thermal transient measurement of insulated gate devices using the thermal properties of the channel resistance and parasitic elements. Issue 12 (December 2015) - Farkas, Gabor; Simon, Gergely
Abstract: The paper discusses thermal transient measurements of advanced devices which operate in a temperature range where linearity cannot be assumed. However, finding a proper physical equation; valid on a wide temperature range for a device category; their calibration can be carried out at convenient temperatures. The validity of the technique can be verified by the good fit of calibrated transients at different power. Some high frequency devices have only a single known stable operation point; the validity of the measurements can be verified by comparing transients of different lengths. In the paper measurements of a device on the RDSON parameter and on reverse diode were compared. Thermal calibration of the RDSON parameter of a FET gives a methodology for measuring the μ n electron mobility. An extension to existing transient standards is suggested. For a more accurate definition of the junction temperature a non-isothermal calculation methodology is outlined.